A thermal conductivity hydrogen sensor ceramic chip and its preparation method
By setting up a gas measurement chamber and a comparison channel in the thermally conductive hydrogen sensor ceramic chip, and using alumina ceramic material and porous platinum materials, the problem of poor hydrogen concentration measurement accuracy in the prior art is solved, and high-precision hydrogen detection is achieved, which is suitable for high-temperature environments.
Patent Information
- Application Number
- CN202411835212.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
AI Technical Summary
The measurement accuracy of hydrogen concentration in existing thermal conductivity hydrogen sensor technologies is poor.
A thermally conductive hydrogen sensor ceramic chip is designed to measure the hydrogen concentration by setting up a gas measurement chamber and a comparison channel by utilizing the resistance changes of the upper electrode, inner electrode and contrast electrode, and improve the measurement accuracy by heating the electrode and porous platinum material.
Through the design of the gas measurement chamber and contrast channel, the measurement accuracy of hydrogen concentration is improved. The use of alumina ceramic materials and porous platinum materials ensures high thermal conductivity and high precision detection, which is suitable for high temperature environments.
Smart Images

Figure CN119738451A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of gas sensing technology, and in particular to a thermal conductivity type hydrogen sensor ceramic chip and a preparation method thereof. Background Art
[0002] Hydrogen leakage and explosion are one of the important causes of safety accidents. It is necessary to detect the hydrogen concentration in the hydrogen use environment and monitor its leakage. Hydrogen sensors are important devices for measuring hydrogen concentration, including semiconductor hydrogen sensors, electrochemical hydrogen sensors and thermal conductivity hydrogen sensors. Among them, thermal conductivity hydrogen sensors rely on the high thermal conductivity of hydrogen for detection and are widely used under high temperature conditions.
[0003] In the prior art, Chinese patent CN117969610A discloses a thermal conductivity hydrogen sensor suitable for high temperature environments, a method of use and a method of preparation. The sensor comprises: a substrate, an internal platinum material layer and a surface platinum material layer; the internal platinum material layer is embedded in the interior of the substrate; the surface platinum material layer covers the surface of the substrate; the head end of the surface platinum material layer adopts a capillary structure; and a grid structure is also provided on the lower side of the capillary structure part.
[0004] However, the above-mentioned prior art determines the hydrogen concentration only by the resistance value of the platinum material, lacks comparative reference, and the measurement accuracy of the hydrogen concentration is poor. Summary of the invention
[0005] The present application provides a thermal conductivity hydrogen sensor ceramic chip and a preparation method thereof, which are used to solve the problem of poor measurement accuracy of hydrogen concentration in the existing thermal conductivity hydrogen sensor technology.
[0006] On the one hand, the present application provides a thermal conductivity hydrogen sensor ceramic chip, including: a first ceramic diaphragm layer, a second ceramic diaphragm layer, a third ceramic diaphragm layer, a fourth ceramic diaphragm layer, a fifth ceramic diaphragm layer and a sixth ceramic diaphragm layer stacked in sequence from top to bottom.
[0007] An upper electrode is arranged on the upper surface of the first ceramic diaphragm.
[0008] The upper surface and the lower surface of the second ceramic diaphragm are both provided with grooves, and the second ceramic diaphragm forms an upper slit and a lower slit with the first ceramic diaphragm and the third ceramic diaphragm respectively through the grooves.
[0009] The second ceramic diaphragm is processed with a gas measurement chamber connected with the upper slit and the lower slit.
[0010] The upper surface and the lower surface of the gas measurement chamber are respectively provided with a first inner electrode and a second inner electrode.
[0011] The fourth ceramic diaphragm is processed with a contrast channel, and the upper surface of the fifth ceramic diaphragm is provided with a contrast electrode, and the contrast electrode is connected to the contrast gas through the contrast channel.
[0012] The upper electrode, the first internal electrode, and the second internal electrode are connected in series.
[0013] In a possible implementation, the first ceramic diaphragm layer, the second ceramic diaphragm layer, the third ceramic diaphragm layer, the fourth ceramic diaphragm layer, the fifth ceramic diaphragm layer and the sixth ceramic diaphragm layer are all made of alumina ceramic material.
[0014] In a possible implementation, the first ceramic diaphragm layer, the second ceramic diaphragm layer, the third ceramic diaphragm layer, the fourth ceramic diaphragm layer, the fifth ceramic diaphragm layer and the sixth ceramic diaphragm layer are all prepared by tape casting process, and the tape casting thickness is in the range of 100-500 μm.
[0015] In a possible implementation manner, a heating electrode is disposed between the fifth ceramic diaphragm and the sixth ceramic diaphragm, and a lower pin electrode is disposed on the lower surface of the sixth ceramic diaphragm.
[0016] The heating electrode is connected in series with the lower pin electrode.
[0017] In a possible implementation, the heating electrode is made of platinum.
[0018] In a possible implementation, the upper electrode is a porous outer electrode or an upper pin electrode.
[0019] The porous outer electrode, the first inner electrode, the second inner electrode, and the comparison electrode are all made of porous platinum material.
[0020] In a possible implementation, the length of the upper slit is 2-10 mm, the width is 1 / 3 to 2 / 3 of the width of the ceramic chip, and the thickness is 8-15 μm.
[0021] The length of the lower slit is 2-10 mm, the width is 1 / 3 to 2 / 3 of the width of the ceramic chip, and the thickness is 10-20 μm.
[0022] On the other hand, the present application provides a method for preparing a thermal conductivity hydrogen sensor ceramic chip, comprising the following steps:
[0023] Step 1: Add adhesive, plasticizer, dispersant, defoamer and organic solvent to ceramic powder, mix and ball-mill to obtain mixed slurry.
[0024] Step 2: putting the mixed slurry into a tape casting machine for tape casting to obtain a film tape.
[0025] Step three, cutting the film strip into film sheets of corresponding sizes according to design requirements, punching holes on the cut film sheets according to drawing requirements, and printing with a printing screen according to design requirements.
[0026] Step 4: stack the printed membrane sheets in order and seal them into blocks, and put the blocks into an isostatic press for pressing, wherein the water temperature of the isostatic press is 50-80°C.
[0027] Step 5: Cut the pressed blocks into green sheets, put them into a sintering furnace and perform degreasing and sintering at 1400-1600° C. to form a thermal conductivity hydrogen sensor ceramic chip.
[0028] In step 4, the block includes: a first layer of ceramic diaphragm, a second layer of ceramic diaphragm, a third layer of ceramic diaphragm, a fourth layer of ceramic diaphragm, a fifth layer of ceramic diaphragm and a sixth layer of ceramic diaphragm which are stacked in sequence from top to bottom; an upper electrode is arranged on the upper surface of the first layer of ceramic diaphragm; grooves are arranged on the upper and lower surfaces of the second layer of ceramic diaphragm, and the second layer of ceramic diaphragm forms an upper slit and a lower slit with the first layer of ceramic diaphragm and the third layer of ceramic diaphragm respectively through the grooves; the second layer of ceramic diaphragm is processed with a gas measurement chamber connected with the upper slit and the lower slit; a first inner electrode and a second inner electrode are arranged on the upper and lower surfaces of the gas measurement chamber respectively; the fourth layer of ceramic diaphragm is processed with a contrast channel, and a contrast electrode is arranged on the upper surface of the fifth layer of ceramic diaphragm, and the contrast electrode is connected to the contrast gas through the contrast channel; the upper electrode, the first inner electrode and the second inner electrode are connected in series.
[0029] A thermal conductivity hydrogen sensor ceramic chip and a preparation method thereof in this application have the following advantages:
[0030] By setting up a gas measurement chamber and a comparison channel, by measuring the resistance of the upper electrode, the first inner electrode, and the second inner electrode and comparing them with the resistance of the comparison electrode, the hydrogen concentration in the gas to be measured can be obtained, thereby improving the measurement accuracy.
[0031] The proposed first ceramic diaphragm, second ceramic diaphragm, third ceramic diaphragm, fourth ceramic diaphragm, fifth ceramic diaphragm and sixth ceramic diaphragm are all made of alumina ceramic material. Alumina ceramic material has high insulation, high thermal conductivity and high temperature resistance, which can effectively prevent hydrogen atoms from penetrating into the contrast channel, thereby ensuring measurement accuracy.
[0032] The proposed heating electrode is made of platinum material. By designing the resistance of the heating electrode, it can meet the use requirements of the thermal conductivity hydrogen sensor ceramic chip in a high temperature environment, ensuring that the sensor as a whole is maintained at a constant temperature. Even when the external ambient temperature fluctuates, the stability and accuracy of its detection performance can be maintained, while extending its service life.
[0033] The proposed porous outer electrode, first inner electrode, second inner electrode, and comparison electrode all use porous platinum material, which greatly increases the contact area between the porous outer electrode, the first inner electrode, the second inner electrode and the gas to be measured, as well as the contact area between the comparison electrode and the comparison gas, thereby improving the detection sensitivity and response speed, and ensuring measurement accuracy even when the hydrogen concentration is low.
[0034] The proposed upper slit has a length of 2-10 mm, a width of 1 / 3 to 2 / 3 of the width of the ceramic chip, and a thickness of 8-15 μm. The proposed lower slit has a length of 2-10 mm, a width of 1 / 3 to 2 / 3 of the width of the ceramic chip, and a thickness of 10-20 μm. By setting the length, width, and thickness of the upper and lower slits within a limited range, the content and flow rate of the gas to be measured entering the gas measurement chamber can be effectively controlled, thereby achieving accurate measurement of the hydrogen concentration and improving the measurement accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 A schematic cross-sectional view of a thermal conductivity hydrogen sensor ceramic chip provided in an embodiment of the present application;
[0037] Figure 2 A schematic cross-sectional view of another thermal conductivity hydrogen sensor ceramic chip provided in an embodiment of the present application.
[0038] Description of reference numerals:
[0039] 1-first layer of ceramic diaphragm, 2-second layer of ceramic diaphragm, 3-third layer of ceramic diaphragm, 4-fourth layer of ceramic diaphragm, 5-fifth layer of ceramic diaphragm, 6-sixth layer of ceramic diaphragm, 21-upper slit, 22-lower slit, 23-gas measurement chamber, 231-first inner electrode, 232-second inner electrode, 41-contrast channel, 42-contrast electrode, 51-heating electrode, 61-lower pin electrode, 11-porous outer electrode, 12-upper pin electrode. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0041] Embodiment 1:
[0042] like Figure 1 As shown, Example 1 of the present application provides a thermal conductivity type hydrogen sensor ceramic chip, including: a first layer of ceramic diaphragm 1, a second layer of ceramic diaphragm 2, a third layer of ceramic diaphragm 3, a fourth layer of ceramic diaphragm 4, a fifth layer of ceramic diaphragm 5 and a sixth layer of ceramic diaphragm 6 stacked in sequence from top to bottom.
[0043] An upper electrode is disposed on the upper surface of the first ceramic diaphragm 1 .
[0044] The upper surface and the lower surface of the second ceramic diaphragm 2 are both provided with grooves, and the second ceramic diaphragm 2 forms an upper slit 21 and a lower slit 22 with the first ceramic diaphragm 1 and the third ceramic diaphragm 3 through the grooves.
[0045] The second ceramic diaphragm 2 is processed with a gas measurement chamber 23 which is in communication with the upper slit 21 and the lower slit 22 .
[0046] The upper surface and the lower surface of the gas measurement chamber 23 are respectively provided with a first inner electrode 231 and a second inner electrode 232 .
[0047] The fourth ceramic diaphragm 4 is processed with a contrast channel 41 , and the upper surface of the fifth ceramic diaphragm 5 is provided with a contrast electrode 42 , and the contrast electrode 42 is connected to the contrast gas through the contrast channel 41 .
[0048] The upper electrode, the first internal electrode 231 , and the second internal electrode 232 are connected in series.
[0049] Specifically, in this embodiment, the upper electrode, the first internal electrode 231 and the second internal electrode 232 are connected in series via a hole-filling slurry column.
[0050] Exemplarily, the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are all made of alumina ceramic material.
[0051] Exemplarily, the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are all prepared by a tape-casting process. In this embodiment, the tape-casting thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 300μm, 100μm, 100μm, 300μm and 300μm, respectively.
[0052] Exemplarily, a heating electrode 51 is disposed between the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 , and a lower pin electrode 61 is disposed on the lower surface of the sixth ceramic diaphragm 6 .
[0053] The heating electrode 51 is connected in series with the lower pin electrode 61 .
[0054] Specifically, in this embodiment, the heating electrode 51 and the lower pin electrode 61 are connected in series via a hole-filling slurry column.
[0055] Exemplarily, the heating electrode 51 is made of platinum.
[0056] Illustratively, in this embodiment, the upper electrode adopts a porous outer electrode 11 .
[0057] The porous outer electrode 11 , the first inner electrode 231 , the second inner electrode 232 , and the reference electrode 42 are all made of porous platinum material.
[0058] Exemplarily, in this embodiment, the length of the upper slit 21 is 2 mm, the width is 1 / 3 of the width of the ceramic chip, and the thickness is 8 μm.
[0059] The length of the lower slit 22 is 2 mm, the width is 1 / 3 of the width of the ceramic chip, and the thickness is 10 μm.
[0060] Specifically, too small a slit width, thickness, and too large a slit length will cause the gas flow rate to be too slow, resulting in a slow change in the hydrogen concentration value of the ceramic chip; too large a slit width, thickness, and too small a slit length will cause the hydrogen concentration value of the ceramic chip to be greatly affected by the airflow, and both cannot accurately measure the gas concentration. By setting the length, width, and thickness of the upper slit 21 and the lower slit 22 within a limited range, the content and flow rate of the gas to be measured entering the gas measurement chamber 23 can be effectively controlled, thereby achieving accurate measurement of the hydrogen concentration and improving the measurement accuracy.
[0061] Embodiment 1 of the present application also provides a method for preparing a thermal conductivity type hydrogen sensor ceramic chip, comprising the following steps:
[0062] Step 1: Add adhesive, plasticizer, dispersant, defoamer and organic solvent to ceramic powder, mix and ball-mill to obtain mixed slurry.
[0063] Step 2: putting the mixed slurry into a tape casting machine for tape casting to obtain a film tape.
[0064] Step three, cutting the film strip into film sheets of corresponding sizes according to design requirements, punching holes on the cut film sheets according to drawing requirements, and printing with a printing screen according to design requirements.
[0065] Step 4: stack the printed membranes in order and seal them into blocks, and put the blocks into an isostatic press for pressing, and the water temperature of the isostatic press is 50°C.
[0066] Step 5: Cut the pressed bar blocks into green sheets, put them into a sintering furnace and perform degreasing and sintering at 1400° C. to form a thermal conductivity hydrogen sensor ceramic chip.
[0067] In step 4, the bar block includes: a first layer of ceramic diaphragm 1, a second layer of ceramic diaphragm 2, a third layer of ceramic diaphragm 3, a fourth layer of ceramic diaphragm 4, a fifth layer of ceramic diaphragm 5 and a sixth layer of ceramic diaphragm 6 stacked in sequence from top to bottom; an upper electrode is provided on the upper surface of the first layer of ceramic diaphragm 1; grooves are provided on the upper and lower surfaces of the second layer of ceramic diaphragm 2, and the second layer of ceramic diaphragm 2 forms an upper slit 21 and a lower slit 22 with the first layer of ceramic diaphragm 1 and the third layer of ceramic diaphragm 3 through the grooves; the second The first ceramic diaphragm 2 is processed with a gas measurement chamber 23 connected with the upper slit 21 and the lower slit 22; the upper surface and the lower surface of the gas measurement chamber 23 are respectively provided with a first internal electrode 231 and a second internal electrode 232; the fourth ceramic diaphragm 4 is processed with a contrast channel 41, and the upper surface of the fifth ceramic diaphragm 5 is provided with a contrast electrode 42, and the contrast electrode 42 is connected with the contrast gas through the contrast channel 41; the upper electrode, the first internal electrode 231, and the second internal electrode 232 are connected in series.
[0068] The hydrogen measurement principle of a thermal conductivity hydrogen sensor ceramic chip in this embodiment is as follows:
[0069] The gas to be measured contacts the upper electrode, and enters the gas measurement chamber 23 through the upper slit 21 and the lower slit 22 to contact the first inner electrode 231 and the second inner electrode 232; when the gas to be measured contains hydrogen, due to the high thermal conductivity of hydrogen, the temperature distribution on the surface of the sensor ceramic chip will change rapidly, and the change in the temperature field will cause the resistance of the upper electrode, the first inner electrode 231, and the second inner electrode 232 to change; while the comparison gas in the comparison channel 41 does not contain hydrogen, and will not affect the resistance of the comparison electrode 42; at the same time, the resistance of the upper electrode, the first inner electrode 231, the second inner electrode 232 and the comparison electrode 42 is also affected by the high temperature ambient temperature provided by the heating electrode 51. By measuring the resistance of the upper electrode, the first inner electrode 231, and the second inner electrode 232, and comparing them with the resistance of the comparison electrode 42, the hydrogen concentration in the gas to be measured can be obtained, thereby improving the measurement accuracy.
[0070] Embodiment 2:
[0071] Illustratively, the difference between Example 2 and Example 1 is that in the preparation method of Example 2, the water temperature of the isostatic press is 65°C, and the temperature of degreasing and sintering is 1500°C.
[0072] In a thermal conductivity type hydrogen sensor ceramic chip of Example 2, the cast thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 100μm, 300μm, 300μm, 100μm and 100μm respectively, the length of the upper slit 21 is 6mm, the width is 1 / 2 of the width of the ceramic chip, and the thickness is 11μm, the length of the lower slit 22 is 6mm, the width is 1 / 2 of the width of the ceramic chip, and the thickness is 15μm.
[0073] The other steps of the preparation method of Example 2, the other structures of the ceramic chip and the hydrogen measurement principle are the same as those of Example 1.
[0074] Embodiment 3:
[0075] Illustratively, the difference between Example 3 and Example 1 is that in the preparation method of Example 3, the water temperature of the isostatic press is 80°C, and the temperature of degreasing and sintering is 1600°C.
[0076] In a thermal conductivity type hydrogen sensor ceramic chip of Example 3, the cast thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 500μm, 200μm, 200μm, 500μm and 500μm respectively, the length of the upper slit 21 is 10mm, the width is 2 / 3 of the width of the ceramic chip, and the thickness is 15μm, the length of the lower slit 22 is 10mm, the width is 2 / 3 of the width of the ceramic chip, and the thickness is 20μm.
[0077] The other steps of the preparation method of Example 3, the other structures of the ceramic chip and the hydrogen measurement principle are the same as those of Example 1.
[0078] Embodiment 4:
[0079] Exemplarily, the difference between Example 4 and Example 3 is that in a thermal conductivity type hydrogen sensor ceramic chip of Example 4, the casting thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 200 μm, 500 μm, 500 μm, 200 μm and 200 μm respectively.
[0080] The preparation method, other structures of the ceramic chip and the hydrogen measurement principle of Example 4 are the same as those of Example 3.
[0081] Embodiment 5:
[0082] Exemplarily, the difference between Example 5 and Example 3 is that in a thermal conductivity hydrogen sensor ceramic chip of Example 5, the casting thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 200 μm, 200 μm, 200 μm, 200 μm, 200 μm, and 200 μm, respectively.
[0083] The preparation method, other structures of the ceramic chip and the hydrogen measurement principle of Example 5 are the same as those of Example 3.
[0084] Embodiment 6:
[0085] Exemplarily, the difference between Example 6 and Example 3 is that in a thermal conductivity type hydrogen sensor ceramic chip of Example 6, the casting thicknesses of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 are 300 μm, 300 μm, 300 μm, 300 μm, 300 μm, and 300 μm, respectively.
[0086] The preparation method, other structures of the ceramic chip and the hydrogen measurement principle of Example 6 are the same as those of Example 3.
[0087] In other possible embodiments, the cast thickness of the first ceramic diaphragm 1, the second ceramic diaphragm 2, the third ceramic diaphragm 3, the fourth ceramic diaphragm 4, the fifth ceramic diaphragm 5 and the sixth ceramic diaphragm 6 can also be set to other thicknesses according to actual conditions.
[0088] Embodiment 7:
[0089] like Figure 2 As shown, illustratively, the difference between Example 7 and Example 1 is that the upper electrode in Example 7 adopts the upper pin electrode 12. The preparation method, other structures of the ceramic chip and the hydrogen measurement principle of Example 7 are the same as those of Example 1.
[0090] The embodiment of the present application sets up a gas measurement chamber 23 and a comparison channel 41, measures the resistance of the upper electrode, the first inner electrode 231, and the second inner electrode 232, and compares them with the resistance of the comparison electrode 42, so as to obtain the hydrogen concentration in the gas to be measured, thereby improving the measurement accuracy.
[0091] The proposed first ceramic diaphragm 1, second ceramic diaphragm 2, third ceramic diaphragm 3, fourth ceramic diaphragm 4, fifth ceramic diaphragm 5 and sixth ceramic diaphragm 6 are all made of alumina ceramic material. Alumina ceramic material has high insulation, high thermal conductivity and high temperature resistance, which can effectively prevent hydrogen atoms from penetrating into the comparison channel 41, thereby ensuring measurement accuracy.
[0092] The proposed heating electrode 51 is made of platinum material. By designing the resistance of the heating electrode 51, the use requirements of the thermal conductivity hydrogen sensor ceramic chip in a high temperature environment can be met, ensuring that the sensor as a whole is maintained at a constant temperature. Even when the external ambient temperature fluctuates, the stability and accuracy of its detection performance can be maintained, while extending its service life.
[0093] The proposed porous outer electrode 11, first inner electrode 231, second inner electrode 232, and comparison electrode 42 are all made of porous platinum material, which greatly increases the contact area between the porous outer electrode 11, first inner electrode 231, second inner electrode 232 and the gas to be measured, and increases the contact area between the comparison electrode 42 and the comparison gas, thereby improving the detection sensitivity and response speed, and ensuring measurement accuracy even when the hydrogen concentration is low.
[0094] The proposed upper slit 21 has a length of 2-10 mm, a width of 1 / 3 to 2 / 3 of the width of the ceramic chip, and a thickness of 8-15 μm. The proposed lower slit 22 has a length of 2-10 mm, a width of 1 / 3 to 2 / 3 of the width of the ceramic chip, and a thickness of 10-20 μm. By setting the length, width, and thickness of the upper slit 21 and the lower slit 22 within a limited range, the content and flow rate of the gas to be measured entering the gas measurement chamber 23 can be effectively controlled, thereby achieving accurate measurement of the hydrogen concentration and improving the measurement accuracy.
[0095] Although the preferred embodiments of the present application have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0096] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A thermal conductivity hydrogen sensor ceramic chip, characterized in that: include: A first ceramic diaphragm layer, a second ceramic diaphragm layer, a third ceramic diaphragm layer, a fourth ceramic diaphragm layer, a fifth ceramic diaphragm layer and a sixth ceramic diaphragm layer are stacked in sequence from top to bottom; An upper electrode is provided on the upper surface of the first ceramic diaphragm; The upper surface and the lower surface of the second ceramic diaphragm are both provided with grooves, and the second ceramic diaphragm forms an upper slit and a lower slit with the first ceramic diaphragm and the third ceramic diaphragm through the grooves respectively; The second ceramic diaphragm is processed with a gas measurement chamber connected to the upper slit and the lower slit; The upper surface and the lower surface of the gas measurement chamber are respectively provided with a first inner electrode and a second inner electrode; The fourth ceramic diaphragm is processed with a contrast channel, and the upper surface of the fifth ceramic diaphragm is provided with a contrast electrode, and the contrast electrode is connected to the contrast gas through the contrast channel; The upper electrode, the first internal electrode, and the second internal electrode are connected in series.
2. A thermal conductivity hydrogen sensor ceramic chip according to claim 1, characterized in that: The first ceramic diaphragm layer, the second ceramic diaphragm layer, the third ceramic diaphragm layer, the fourth ceramic diaphragm layer, the fifth ceramic diaphragm layer and the sixth ceramic diaphragm layer are all made of alumina ceramic material.
3. A thermal conductivity hydrogen sensor ceramic chip according to claim 2, characterized in that: The first ceramic diaphragm layer, the second ceramic diaphragm layer, the third ceramic diaphragm layer, the fourth ceramic diaphragm layer, the fifth ceramic diaphragm layer and the sixth ceramic diaphragm layer are all prepared by tape casting process, and the tape casting thickness is in the range of 100-500 μm.
4. A thermal conductivity hydrogen sensor ceramic chip according to claim 1, characterized in that: A heating electrode is arranged between the fifth ceramic diaphragm and the sixth ceramic diaphragm, and a lower pin electrode is arranged on the lower surface of the sixth ceramic diaphragm; The heating electrode is connected in series with the lower pin electrode.
5. A thermal conductivity hydrogen sensor ceramic chip according to claim 4, characterized in that: The heating electrode is made of platinum.
6. The thermal conductivity hydrogen sensor ceramic chip according to claim 1, characterized in that: The upper electrode is a porous outer electrode or an upper pin electrode; The porous outer electrode, the first inner electrode, the second inner electrode, and the comparison electrode are all made of porous platinum material.
7. The thermal conductivity hydrogen sensor ceramic chip according to claim 1, characterized in that: The length of the upper slit is 2-10 mm, the width is 1 / 3 to 2 / 3 of the width of the ceramic chip, and the thickness is 8-15 μm; The length of the lower slit is 2-10 mm, the width is 1 / 3 to 2 / 3 of the width of the ceramic chip, and the thickness is 10-20 μm.
8. A method for preparing a thermal conductivity type hydrogen sensor ceramic chip according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, adding a binder, a plasticizer, a dispersant, a defoamer, and an organic solvent to the ceramic powder, mixing and ball-milling the mixture to obtain a mixed slurry; Step 2, placing the mixed slurry into a tape casting machine for tape casting to obtain a film tape; Step 3, cutting the film strip into film sheets of corresponding sizes according to design requirements, punching holes on the cut film sheets according to drawing requirements, and printing with a printing screen according to design requirements; Step 4: stack the printed membranes in order and seal them into blocks, and put the blocks into an isostatic press for pressing, wherein the water temperature of the isostatic press is 50-80°C; Step 5, cutting the pressed bar blocks into green sheets, placing them in a sintering furnace for degreasing and sintering at 1400-1600° C. to form thermal conductivity hydrogen sensor ceramic chips; In step 4, the block includes: a first layer of ceramic diaphragm, a second layer of ceramic diaphragm, a third layer of ceramic diaphragm, a fourth layer of ceramic diaphragm, a fifth layer of ceramic diaphragm and a sixth layer of ceramic diaphragm which are stacked in sequence from top to bottom; an upper electrode is arranged on the upper surface of the first layer of ceramic diaphragm; grooves are arranged on the upper and lower surfaces of the second layer of ceramic diaphragm, and the second layer of ceramic diaphragm forms an upper slit and a lower slit with the first layer of ceramic diaphragm and the third layer of ceramic diaphragm respectively through the grooves; the second layer of ceramic diaphragm is processed with a gas measurement chamber connected with the upper slit and the lower slit; a first inner electrode and a second inner electrode are arranged on the upper and lower surfaces of the gas measurement chamber respectively; the fourth layer of ceramic diaphragm is processed with a contrast channel, and a contrast electrode is arranged on the upper surface of the fifth layer of ceramic diaphragm, and the contrast electrode is connected to the contrast gas through the contrast channel; the upper electrode, the first inner electrode and the second inner electrode are connected in series.
Citation Information
Patent Citations
Thermal conductivity type hydrogen sensor applicable to high-temperature environment, use method and preparation method
CN117969610A